APPROACHES IN CONDUCTING PRIMARY PREVENTION OF TENDENCY OF MAXILLARY CANINE IMPACTION IN THE LATE MIXED DENTITION. - Hristina Arnautska (Peytchinski Publishing, 2015)
Early diagnosis and prediction of potential maxillary canine impaction are of essential importance for the normal formation of dentition. The aim of this article is to present a protocol for primary prevention of potential maxillary canine impaction in the late mixed dentition. The diagnostic protocols include three methods of examination - anamnestic, clinical and radiological, and depending on the obtained results, the protocol for phase 1 of the late mixed dentition directs to three clinical preventive approaches of action. In phase 2 of the late mixed dentition, the clinical approaches are two, due to the approaching time of eruption of the canine and the need for immediate treatment measures. We believe that the most useful preventive interventions should take place during the early mixed dentition and phase 1 of the late mixed dentition. Early extraction of the temporary canine will lead to a change in the eruption path of the permanent canine - up righting and eruption in the normal position in the dental arch - if there is enough space.